Assessing the statistical properties and underlying model structure of fifteen safety constructs. (April 2017) - van Kampen, Jakko; van der Beek, Dolf; Steijn, Wouter; Groeneweg, Jop; Guldenmund, Frank
Highlights: Certain operational process are related to the occurrence of incidents. An instrument was developed for mapping and quantification these process. Construct validity and the dimensional structure of the instrument were established. Confirmatory factor analysis presented acceptable fit across multiple datasets. Abstract: Background: Organisations spend a considerable amount of time and effort on diagnosing and analysing risks within their organisation. In the area of occupational and process safety, a myriad of employee survey instruments is available. Many studies show that operational processes play an important role in an organisations overall safety. Yet, so far safety surveys mainly focus on safety measures or operational safety processes. A flexible instrument was developed with which a wide variety of constructs, from different disciplines, can be measured in a consistent and practical way. The resulting survey distinguishes itself from existing safety surveys by extending the scope with the operational processes which are also referred to as the 'Core Business'. Study: This study reports on the development of a catalogue of constructs which were derived from scientific literature and practice. Each of these constructs has been developed with a view towards measurability in an employee survey. The reliability and validity for fifteen of these constructs was assessed. Five separate projects have been conducted within a range of organisations operating as high risk industries. Results: Construct validity and the dimensional structure of the instrument have been established through exploratory factor analysis and confirmed through confirmatory factor analysis. Diverse aspects derived from motivational and ergonomic approaches to safety proved to be distinguishable in this analysis. Conclusion: The described instrument allows the mapping and quantification of various aspects of the operational process that are, based on existing knowledge, related to the occurrence of incidents.